Rol del liderazgo ético en organizaciones académicas (2016)
The purpose of the article was to analyze ethical leadership and its role to academic organizations, for which it was based on the methodology of hermeneutics through literature and document review. In conclusion, the ethical values that guide the behavior and conduct of employees of academic organizations, creating an atmosphere of commitment and social consciousness based on ethical leadership base. In addition, academic organizations that ethics is conceived as guiding principles that guide people in their conception of life, man, judgments, facts, and morality. Similarly, ethical leadership recognizes the ability to take the service to others, highlighting the relevance of academic organizations need to improve the living conditions of the people, as well as in the welfare and progress of society. So the role of ethical leadership in academia should be made up of officials aimed at achieving purposes of ethical values to the university community and society.